Uncertainty and Safety. Or how I learned to stop worrying and love autonomy - Griffin, Mark (2019)
Across all fields of management research, uncertainty is largely considered an aversive state that people and organizations cope with unwillingly and generally aim to avoid. However, theories based on principles of uncertainty reduction overlook opportunities arising from uncertainty creation. Building on recent research in management, cognition and neuroscience, we expand current conceptualizations of uncertainty by introducing a model of uncertainty regulation where individuals employ opening and closing behaviors to achieve alignment between preferred and experienced levels of uncertainty and with exogenous requirements for effectiveness. We derive propositions for uncertainty regulation and work performance which extend existing concepts of adaptation in uncertain environments to include deliberate uncertainty creation and expansive agency. We discuss implications for dynamic models of agentic goal striving, organizational support for individuals' uncertainty regulation, and extensions to team- and organization-level phenomena